The 'burden' of traceability in gold supply chains. (1st June 2020) - Finlay, David
Abstract : Artisanal and Small-scale Mining (ASM) constitutes 15% (600 tonnes) of global gold production but, as a sector, remains largely veiled to both businesses and consumers in developed Western markets. The movement towards the 'responsible sourcing' of such gold is beginning to gain traction, especially in the jewellery sector, but has started some two decades after equivalent movements for responsible coffee, cocoa and tea, and is accompanied by its own - often surprising - challenges. This article provides an overview of both the ASM landscape and the challenges facing miners and supply chain actors in delivering responsibly mined gold to the point of end-consumer products. It concludes with two examples of mass-balance models that Fairtrade is introducing to drive increases in the volumes of responsibly mined gold sold from mine sites, which accounts for and responds to the 'burden' of full traceability for both large- and small-scale supply chain actors.